Climbers for Bat Conservation: creating a citizen science program in Red River Gorge Kentucky - Gross, Emily E.; Siebka, Morgan E.; Schorr, Robert A.; Solomon, Jennifer N.; Davis, Shawn K. (Frontiers in Communication, 2023)
In recent years, North American bat populations have been presented with new conservation threats including White Nose Syndrome. As these threats continue to impact bats it is important to locate and study these populations. Though most bats tend to roost and hibernate in caves, still many roost in cracks, crevices, and other hard to reach places. Rock climbers recreate on a large array of rock features that are inaccessible or unknown to bat biologists and could serve as a valuable resource in identifying the location of bat species for conservation efforts. Yet, developing and maintaining a productive relationship between recreationists and the conservation community can be challenging, making environmental communication vital to successful collaborative efforts. We explored rock climbers’ willingness to participate in a citizen science program for reporting bat sightings through Climbers for Bat Conservation (CBC) while at Red River Gorge (RRG), Kentucky. We utilized a mixed methods case study consisting of a world café facilitated dialog with members of a local climbing organization, bat biologists, land managers, and landowners (n = 18) as well as semi-structured interview data (n = 12) collected at a local climbing festival. Results indicate mutual importance given to bats, climbing, and conservation from world café attendees. Additionally, attendees identified three key parts of a bat observation that would be critical data for rock climbers to report which included presence of a bat, the location, and the climbing route name. Finally, attendees identified having a local climbing ranger or climbing liaison as important to organizing other climbers to submit data. Interview data revealed that the most mentioned barriers to submitting a bat report were awareness of CBC, time, convenience, forgetfulness, fear of route closures, and access to a phone. A discussion follows detailing how this information may be used to further the design and implementation of a citizen science program as well as increase climber engagement at RRG.